Control interno de los bienes patrimoniales y los estados financieros de la Municipalidad Provincial de Contamana, 2023 - Pasquel Flores, Fernando (2023)
The investigation developed with the objective of verifying the relationship between the internal control of patrimonial assets and the financial statements of the Provincial Municipality of Contamana, 2023; therefore, it is specified that it was of a basic type, with a descriptive and correlational approach, as well as a non-experimental design, for which it took 50 collaborators as a sample, the survey was the ideal technique to know the perception of these people, and registered in a questionnaire. After processing and analyzing the results, the work concluded that the control of assets is qualified by 62% as adequate, likewise, the management and interpretation of financial statements are qualified by 58% of workers as adequate. In general, it was determined that the internal control of assets and financial statements maintain an average positive relationship of 69.8% in 2023, in addition, the control environment (56.9%), risk assessment (75.6%), control activities (43.2%), as well as information and communication (61.3%) establish a positive and significant relationship with the management and interpretation of financial statements.